RBM10 Regulates Embryonic Trophoblast Injury via Endoplasmic Reticulum Stress - Xiao Chen; Juan Du; Liyu Chen; Lanlan Wang; Gang Xin (IMR Press, 2022)
Background: Previous studies shown that RNA binding motif proteins (RBM) participate in regulating various physiological processes such as cell autophagy, proliferation, and apoptosis, and are abnormally highly expressed in placental trophoblast cells intervened by hypoxia in vitro, but their molecular mechanisms regulating placental trophoblast damage remain unclear. This study aims to investigate the role and molecular mechanism of RBM10 in regulating hypoxia-induced placental trophoblast injury through endoplasmic reticulum stress. Methods: CCK-8 cell proliferation assay and Transwell cell invasion assay were applied to detect the proliferation and invasion ability of normal, hypoxic and RBM10 up-regulated plus hypoxic embryonic trophoblast cells, respectively. The expression of endoplasmic reticulum stress-related proteins (ERN-1) and C/EBP homologous protein (CHOP), apoptosis-related proteins B cell lymphoma-2 (Bcl-2), Bcl-2-associated X protein (Bax) and Caspase-3, and autophagy-related proteins including microtubule-associated protein 1 light chain 3 (LC-3), Beclin-1 and P62 were also detected by western blot assays. The effects of hypoxia and overexpression of RBM10 on placental trophoblast apoptosis were examined using flow cytometry. Results: We found that the growth and invasion ability of placental trophoblast cells treated with hypoxia were significantly decreased (p < 0.05), and the upregulation of RBM10 further led to the decrease of the growth and invasion ability of hypoxic placental trophoblast cells. In addition, hypoxia promoted the expression of endoplasmic reticulum stress-related proteins (p < 0.05), which triggered apoptosis and autophagy of embryonic trophoblast cells. The data showed that embryonic trophoblast cells regulated cell injury by stimulating endoplasmic reticulum stress after hypoxia. after upregulation of RBM10 expression, the expression levels of endoplasmic reticulum stress-related proteins ERN-1 and CHOP were further increased (p < 0.05), and the apoptosis rate of embryonic trophoblast cells was further increased (p < 0.05). Conclusions: Overall, our findings suggest that post-hypoxia mediates autophagy in embryonic trophoblast cells through stimulation of endoplasmic reticulum stress, thereby promoting apoptosis. Overexpression of RBM10 levels regulates the proliferative, apoptotic capacity of trophoblast cells by affecting cellular endoplasmic reticulum stress. RBM10 plays an important role in regulating hypoxia-induced autophagy and apoptosis in trophoblast cells, and RBM10 upregulation can further stimulate endoplasmic reticulum stress-mediated autophagy and apoptosis in trophoblast cells.